A study on Training & Development on a Particular Department: (Recruitment & Selection Process) of MIR Group of Company Limited. - Joy, Ismam Atik (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.